Emerging application of biochar as a renewable and superior filler in polymer composites - Tengku Yasim-Anuar, Tengku Arisyah; Yee-Foong, Lawrence Ng; Lawal, Abubakar Abdullahi; Ahmad Farid, Mohammed Abdillah; Mohd Yusuf, Mohd Zulkhairi; Hassan, Mohd Ali; Ariffin, Hidayah (Royal Society of Chemistry, 2022)
Biochar is conventionally and widely used for soil amendment or as an adsorbent for water treatment. Nevertheless, the need for transition to renewable materials has resulted in an expansion of biochar for use as a filler for polymer composites. The aim is to enhance the physical, chemical, mechanical and rheological properties of the polymer composite. The reinforcement of biochar into a polymer matrix however is still new, and limited reports are focusing on the effects of biochar towards polymer composite properties. Hence, this review highlights the unique properties of biochar and its effect on the crystallization, thermal, flammability, electrical conductivity, and mechanical properties of polymer composites. This review does not solely summarize recent studies on biochar–polymer-based composites, but also offers insights into a new direction of biochar as a renewable and superior polymer filler in the future.